The Main Factors Affecting the Selection of Courses Related to Food Services among Male Students in Vocational Colleges - Tukiran, Nor Anis Intan Aqiah; Ahmad, Nor Aziah; Syawal Ismail, Lisa Mariam; Zakariah, Siti Hajar; Harun, Haruddin (Online Journal for TVET Practitioners, 2021)
The increase in intake of students in vocational colleges is now increasing and getting a place among students. The field of culinary art and bakery pastry or better known as food service is one of the areas of skill that is getting a place among students. However, the lack of male students in this field is significantly compared to female students who have a high number of men. The purpose of this study is to identify the main factors affecting the selection of courses related to the food service among male students in vocational colleges and identify the differences between the factors that influence the course selection associated with food services among male students in vocational colleges. Samples of the study were male study in certificate and culinary arts diploma and bakery and vocational college pastry, which was 86 respondents. The research design used was a purposive sampling method using questionnaire forms for collecting data. The data obtained were analyzed using descriptive analysis to see the frequency, percentage, mean score and standard deviation and ANOVA inferential analysis using Statistical Packages for Social Science (SPSS) version 25. The findings show that the factors of interest, the influence factor of parents and the career selection factors were at high level. Through this study, there were significant differences (p <0.05) in among the factors affecting the selection of courses related to food services. The results of this study can be a guide to vocational colleges and education ministries to make improvements in improving the quality of the course to attract more male students in the field of food services.